2023
DOI: 10.1038/s41598-023-34828-y
|View full text |Cite
|
Sign up to set email alerts
|

Underweight and risk of fractures in adults over 40 years using the nationwide claims database

Abstract: We aimed to investigate how underweight affects the incidence of fractures, as well as the influence of cumulative, longitudinal periods of low body mass index (BMI) and changes in body weight on fracture development. Data on adults aged 40-year and over who had three health screenings between January 1, 2007, and December 31, 2009 were used to determine the incidence of new fractures. The hazard ratios (HRs) for new fractures depending on BMI, total cumulative number of underweight, and weight change over tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…For example, Finkelstein et al reported a strong association between body mass index and the probability of sustaining an injury [ 25 ]. Vice versa, not obesity but underweight is a known risk factor for fractures, since obesity is usually not associated with an increased risk of fractures [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Finkelstein et al reported a strong association between body mass index and the probability of sustaining an injury [ 25 ]. Vice versa, not obesity but underweight is a known risk factor for fractures, since obesity is usually not associated with an increased risk of fractures [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This age and nutritional disparity can inherently influence the outcomes of studies involving these populations. For instance, underweight is a risk factor for OP [ 49 , 50 ] and while obesity stimulates the development of OA [ 19 , 50 ] and maybe acts as OP protector factor [ 51 ]. Additionally, functional capacity is an independent factor for hip fracture [ 52 ], whereas hip arthroplasty is a common treatment for OA patients [ 53 ].…”
Section: Discussionmentioning
confidence: 99%